Pengembangan Usaha Sapi Potong Berbasis Tenaga Kerja Keluarga Di Kecamatan Wonosari Kabupaten Gunung Kidul - Soumokil, Fisca M; Rehatta, Lea M (Universitas Pattimura, 2024)
One of the most promising livestock businesses is beef cattle. Generally, beef cattle businesses applied in Indonesia are relatively small-scale, so they still need to meet domestic beef needs. This study aims to study the development of the beef cattle business in the Wonosari sub-district, Gunung Kidul Regency. This research is survey research. The sample villages were determined by purposive sampling, namely villages with the largest livestock population. Respondents are carried out on a quota basis. The sample from each village was 15 farmers for three villages, with 45 farmer respondents. The analysis carried out is descriptive. The results showed that family labor for each activity in beef cattle management from the largest is foraging on their land, giving feed, giving water, cleaning pens, cultivating agricultural land, and treating livestock.